2017
DOI: 10.1038/emi.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Additional molecular testing of saliva specimens improves the detection of respiratory viruses

Abstract: Emerging infectious diseases in humans are often caused by respiratory viruses such as pandemic or avian influenza viruses and novel coronaviruses. Microbiological testing for respiratory viruses is important for patient management, infection control and epidemiological studies. Nasopharyngeal specimens are frequently tested, but their sensitivity is suboptimal. This study evaluated the incremental benefit of testing respiratory viruses in expectorated saliva using molecular assays. A total of 258 hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
145
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 43 publications
(63 reference statements)
2
145
0
4
Order By: Relevance
“…Consistently, in the present study, we obtained higher positive rates when using BALF and sputum samples than when using NPS, although the difference was not significant (78.8% vs 61.5%, P = .166). Moreover, in recent years, saliva has also shown potential as a suitable material for the molecular detection of respiratory viruses …”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in the present study, we obtained higher positive rates when using BALF and sputum samples than when using NPS, although the difference was not significant (78.8% vs 61.5%, P = .166). Moreover, in recent years, saliva has also shown potential as a suitable material for the molecular detection of respiratory viruses …”
Section: Discussionmentioning
confidence: 99%
“…If patients were intubated, we obtained endotracheal aspirate instead of posterior oropharynx saliva. 6,[9][10][11] Our initial experience showed that such saliva samples are promising in viral load monitoring in patients with COVID-19. 6 We also retrieved serum remnant from blood samples taken for routine bio chemical testing, and refrigerated these samples at -20°C until antibody testing could be done.…”
Section: Methodsmentioning
confidence: 99%
“…Saliva specimens were tested for respiratory viruses using NxTAG™ Respiratory Pathogen Panel IVD (Luminex, Austin, TX, USA) as described previously [22,25]. Differentiation of rhinovirus and enterovirus was performed by sequence analysis of the VP4/ VP2 gene region.…”
Section: Study Setting and Designmentioning
confidence: 99%